2021
DOI: 10.3390/ijerph18179018
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences and Predictors of In-Hospital Mortality among Patients with COVID-19: Results from the ANCOHVID Multicentre Study

Abstract: Spain is one of the countries most affected by the COVID-19 pandemic. Although risk factors for severe disease are published, sex differences have been widely neglected. In this multicentre study, we aimed to identify predictors of in-hospital mortality in men and women hospitalised with COVID-19. An observational longitudinal study was conducted in the cohort of patients admitted to four hospitals in Andalusia, Spain, from 1 March 2020 to 15 April 2020. Sociodemographic and clinical data were collected from h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
1
5
1
Order By: Relevance
“…For example, on the site of Johns Hopkins University dedicated to COVID-19 [ 1 ], data clearly shows this influence on the case fatality rate corresponding to the cumulative deaths recorded 5 months after the beginning of the outbreak (12 May 2020) vs. the median age of many countries in 2017 ( Figure 1 ). This first observation has been confirmed by many studies in different countries [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] such as in France ( Figure 2 ), and we will confirm in this paper that the age of the patients suffering from COVID-19 is a good predictor of severity.…”
Section: Introductionsupporting
confidence: 85%
“…For example, on the site of Johns Hopkins University dedicated to COVID-19 [ 1 ], data clearly shows this influence on the case fatality rate corresponding to the cumulative deaths recorded 5 months after the beginning of the outbreak (12 May 2020) vs. the median age of many countries in 2017 ( Figure 1 ). This first observation has been confirmed by many studies in different countries [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] such as in France ( Figure 2 ), and we will confirm in this paper that the age of the patients suffering from COVID-19 is a good predictor of severity.…”
Section: Introductionsupporting
confidence: 85%
“…Nonetheless, we consider that our results could be reasonably representative of the Spanish healthcare system at the population and cost-analysis level. At the population level, unlike other studies that represented only one area or autonomous region [ 9 , 10 , 19 , 42 ], our database included data from COVID-19 patients in 17 hospital catchment areas across four regions in Spain (Autonomous Community of Madrid, Castilla and Leon, Catalonia, and Galicia), covering an extensive and diverse demographic population. In addition to the extensive geographic area, HM Hospitals put their facilities at the public administration’s disposal and absorbed COVID-19 patients from public hospitals during the outbreaks, treating more than 40,000 COVID-19 patients during 2020 [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-modifiable risk factors: Moreover, and similar to CVD, age and sex are risk factors for severe COVID-19 ( Fernandez-Martinez et al, 2021 ; Wehbe et al, 2021 ). Italy, hit hardly by the first wave in early 2020, reported that patients older than 64 years had an increased mortality risk compared to younger individuals ( Grasselli et al, 2020 ) and people with more than 70 years of age even displayed a case fatality rate of 22.7% ( Onder et al, 2020 ).…”
Section: Sars-cov-2mentioning
confidence: 99%